The Effects of COVID 19 on Students’ Learning and Wellbeing in Malaysian Higher Education Institutions - Abd Rahman Ahmad; Steven Eric Krauss; Ismi Arif Ismail; Habibah Ab Jalil; Mohd Shahir Shamsir Omar (Communications of International Proceedings, 2021)
The study aims to explore the effect of covid 19 Learning and Wellbeing between two public universities in Malaysia as well as to get in a deep understanding of how students react to the current crisis in their learning activities. Data were collected through a set of online questionnaires distributed to the student via social media and Survey Monkey. Here, data were collected from 26th March to 3rd April 2020 during the Mandatory Control Order (MCO) was being executed. The correspondents of the study included both undergraduate and postgraduate students with total respondents of 10,527 from two universities namely University Tun Hussein Onn Malaysia (UTHM) and University Pendidikan Sultan Idris (UPSI). Results pointed out that the majority of students were significantly anxious and found it difficult to work effectively from home or on the campus during the early period of the outbreak. Online learning makes the student difficult to stay focused during the lectures from home. This study might help the university leader to get a better understanding of the learning challenges that students face during the crisis. Here, university leaders should consider the possible impact of the COVID-19 on students and logistical and psychosocial resources that are needed to fulfill the students’ needs. The study finds that students’ learning with Universities of UTHM and UPSI. The study was conducted to capture the state students’ well-being and learning effectiveness during the COVID-19 pandemic. Hence, this study provides clear insights regarding student learning and well-being during a coronavirus outbreak.
Keywords: student learning; well-being; online learning; higher education; and COVID-19